LabPrac Methods - Bazydlo, Caroline; Biernacki, Alexandra; Sathiyanarayanan, Oviya; Yong, Jenny; Goodwin, Soleil; Mesha, Julie; Syed, Ahad; Ephrem, Cassie (Integrated Science Program, 2025)
In ISCI 2A18, students complete a 5-week supervised Enrichment Project aimed at providing them with a more independent opportunity to further explore a topic introduced in one of the second year projects. Students with an interest in developing research proficiency and hands-on laboratory skills complete a self-guided project in Laboratory Practicum methods under the guidance of the Laboratory Coordinator. The result of their efforts is a written report with a focus on technique development. These accounts are formatted to resemble a publicly accessible scientific article, and compiled to create each issue of LabPrac Methods.
LabPrac Methods 2025
Keywords: Laboratory Practicum; Enrichment Project